Structure-Activity Relationship and Molecular Docking of a Kunitz-Like Trypsin Inhibitor, Kunitzin-AH, from the Skin Secretion of Amolops hainanensis - Yuqing Chen; Xinping Xi; Chengbang Ma; Mei Zhou; Xiaoling Chen; Zhuming Ye; Lilin Ge; Qinan Wu; Tianbao Chen; Lei Wang; Hang Fai Kwok (MDPI AG, 2021)
Kunitz-like trypsin inhibitors are one of the most noteworthy research objects owing to their significance in pharmacological studies, including anticarcinogenic activity, obesity regulation and anticoagulation. In the current study, a novel Kunitz-like trypsin inhibitor, Kunitzin-AH, was isolated from the skin secretion of Amolops hainanensis. The novel peptide displayed a modest trypsin inhibitory activity with the inhibitor constant (Ki) value of 1.18 ± 0.08 µM without inducing damage to healthy horse erythrocytes. Then, a series of shortened variants of Kunitzin-AH were designed by truncating a peptide loop and site mutation inside the loop to illustrate the structure-activity relationship of the trypsin inhibition function. Among the variants, a significant decrease was observed for the Cys-Cys loop domain, while the extension of an Arg at N-terminus (RCKAAFC) retained the inhibitory activity, indicating that the -RCK-motif is essential in forming the reactive domain for exerting the inhibitory activity. Furthermore, substitutions of Ala by hydrophobic or hydrophilic residues decreased the activity, indicating suitable steric hindrance provides convenience for the combination of trypsin. Additionally, the conformational simulation of the analogues processed with Chimera and Gromacs and further combination simulations between the peptides and trypsin conducted with HDOCK offered a potential opportunity for the natural trypsin inhibitory drug design. The truncated sequence, AH-798, may be a good replacement for the full-length peptide, and can be optimized via cyclization for further study.